Uji parasitik Beberapa Spesies Jamur Tanah terhadap Globodera rostochiensis (Woll.) Secara In Vitro - Kalay, A. Marthin; Natasasmita, S; Suganda, T; Simarmata, T (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2008)
Potato cyst nematode (Globodera rostochiensis Woll.) is an important plant pathogen on potatoes. The development of this nematode in soil could be controlled by using soil fungi. In vitro assay to determine the capacity of soil fungi Fusarium oxysporum TR1, F. solani TR2, F. oxysporum KT1, F. chlamydosporum KT2, F. oxysporum SM1, Paecilomyces lilacinus SM3, and F. chlamydosporum SM4 to parasite G. rostochiensis has been cariied out. The results showed that all of tested fungal species enable to reduce the number of living J2 out from the cyst. The highest J2 reduction, 67.48%, was evidence by using P. lilacinus.